NEW VARIETY OF ALKALI-DEFICIENT CHROME-ALUMINUM DRAVITE - Osipov P.V.; Stolpovskaya V.N. (My University, 1990)
Chromium is a common isomorphic admixture in tourmaline from ultramafic plutons. The chromium-containing tourmaline that we found in the Sarykulboldy chrysoprase deposites (Central Kazakhstan) has several distinctive properties. Thus, it is deficient in alkali metals and is rich in chromium and aluminum, and its crystal properties resemble those of synthetic alkali-free alumina-containing dravite, whose composition can be represented as O(Mg2Al)3Al6(BO3)3(Si6O18)(OH)4. We find that our tourmaline differs from those previously known, but is convergent with alumodravites in terms of certain characteristics, especially chemical composition. What we have is a new dravite with anomalously high aluminum content. This suggests that minerals of this type are more widespread in nature than previously thought and thus that this series is more heterogeneous than heretofore assumed. Thus, the tourmaline-containing quartz veins occur within rocks of ultramafic composition but are not genetically associated with them. They are derivatives of the granite intrusion, specifically of the hydrothermal solutions generated by it, which then evolved in the course of migration through the ultramafic rock sequence. In the reactions with the ultramafic rocks, the alkali metals were lost from the solutions, which by contrast became rich in chromium and to some extent in magnesium. The resulting solutions were the source from which the chrome-aluminum low-alkali dravite was crystallized.